Development of functional foods from grouper fish-bone residues to enhance muscle strength and exercise endurance in mice - Kao, Yi-Feng; Chai, Huey-Jine; Tsai, Cheng-Jeng; Tsai, Tsung-Yu; Liu, Te-Hua; Yi, Tsung-Kai; Chen, Yi-Ming (Frontiers in Sustainable Food Systems, 2024)
Grouper aquaculture is a key industry in Taiwan, yet its processing generates significant byproducts, leading to challenges in waste management and environmental sustainability. Recent research has focused on developing innovative methods to valorize these byproducts, with grouper bone hydrolysate (GBH) emerging as a potential candidate for applications in health promotion and exercise performance enhancement. In this study, we investigated the amino acid composition of grouper bone hydrolysate (GBH) and analyzed its peptide contents. We also investigated GBH supplementation in relation to body composition and exercise performance in mice. Male Institute of Cancer Research (ICR) mice were divided into 3 groups (n = 7 per group) and orally administered GBH once daily for 6 weeks at doses of 0 g/kg/day (vehicle), 103 mg/kg/day (GBH-1X), 205 mg/kg/day (GBH-2X), and 513 mg/kg/day (GBH-5X). The GBH was rich in branched-chain amino acids and bioactive peptides, and supplementation enhanced the exercise performance of the mice. GBH supplementation increased their exhaustive swimming time, forelimb grip strength, and tissue glycogen content while reducing fatigue markers such as lactate, ammonia, and creatine kinase. The results indicate that GBH contains dipeptides such as Leu-Ala, Glu-Asp., Met-Leu, Met-Ile, Phe-Pro, Trp-Asp., Leu- Val, and Leu-Cys, as well as tetrapeptides such as Pro-Ser-Met-Ala, Ser-Val-Pro- Ile, and Ala-Val-Pro-Trp. GBH supplementation could aid in overcoming fatigue during endurance exercise and decrease metabolic waste after acute exercise.